AN ANALYSIS OF LEARNING ACTIVITIES IN TEACHING ENGLISH BASED ON THE CURRICULUM 2013 - ., Kadek Alit Putri Adriani; ., Prof. Dr. Dewa Komang Tantra,Dip.,App.; ., Luh Diah Surya Adnyani, S.Pd. (Universitas Pendidikan Ganesha, 2016)
Penelitian ini bertujuan untuk menganalisis kegiatan pembelajaran di pengajaran Bahasa Inggris pada Kurikulum 2013. Subjek dari penelitian ini adalah kegiatan pembelajaran di kelas Bahasa Inggris pada siswa kelas 8. Analisis isi digunakan untuk mengevaluasi kesesuaian dari kegiatan pembelajaran di RPP dengan kegiatan pembelajaran di pedoman guru. Observasi diadakan untuk mengevaluasi kesesuaian antara kegiatan pembelajaran dengan implementasi dikelas. Interview juga diadakan untuk mendapatkan data yang lebih mendalam mengenai penelitian. Hasil dari penelitian ini, pada RPP guru 1, hanya satu kegiatan pembelajaran yang sesuai dengan pedoman guru sedangkan pada RPP guru 2, terdapat 4 kegiatan pembelajaran yang sesuai dengan pedoman guru. Kenyataannya, hasil interview membuktikan bahwa guru tidak menggunakan pedoman guru sebagai acuan dalam membuat RPP, jadi kegiatan pembelajaran yang sesuai hanya suatu kebetulan. Pada implementasi dikelas, tidak ada kegiatan pembelajaran yang sesuai dengan RPP yang telah dibuat guru. Jadi, guru tidak menggunakan pedoman dalam menentukan kegiatan pembelajaran di RPP dan mereka tidak mengimplementasikan dikelas.Kata Kunci : Kurikulum 2013, Kegiatan Pembelajaran, RPP, dan Pedoman Guru This study aimed at analyzing the learning activities in teaching English based on the Curriculum 2013. The subject of this study was the learning activities in English class at the Eight Grade students. Content analysis was used in evaluating the consistency of the learning activities in the lesson plan with the learning activities in the teacher?s guideline. Observation was conducted to evaluate the consistency of the learning activities in the lesson plan with the learning activities in the classroom implementation. Interview was also conducted in order to get deeper data regarding with the research. As the result, in the lesson plan of the Teacher 1, there is only one learning activity consistent with the teacher?s guideline while in the lesson plan of the Teacher 2, there are four activities consistent with the teacher?s guideline. In fact, the result of the interview proved that the teacher didn?t use the teacher?s guideline in making lesson plan, therefore the consistent learning activities are only incidental. In the classroom implementation, there are no planned learning activities implemented by the teacher. Therefore, the teachers do not use the teacher?s guideline in determining learning activities in the lesson plan and they do not also implement the planned learning activities in the classroom.keyword : Curriculum 2013, Learning Activities, Lesson Plan, and Teacher?s Guideline